Theoretical designing and experimental fabricating unique quadruple multimetallic phosphides with remarkable hydrogen evolution performance. (April 2017) - Gu, Wenling; Gan, Linfeng; Zhang, Xiaoyan; Wang, Erkang; Wang, Jin
Abstract: Combined with the theoretical calculations, electrocatalysts for hydrogen evolution reaction (HER) with unprecedented catalytic performance compared to Pt/C are rationally designed and synthesized. Herein, we perform the density functional theory (DFT) calculations to predict remarkable catalytic performance of Fe0.33 Co0.33 Ni0.33 P for the close to zero free energy value of hydrogen absorption. Based on the theoretical prediction, a series of highly efficient homogeneous quadruple multimetallic phosphides of Fex Coy Niz P (where x+y+z=1) nanosheet for HER was successfully prepared. Surprisingly, the experimental results were in agreement with the theoretical prediction. The afforded Fe0.33 Co0.33 Ni0.33 P electrocatalyst exhibits the lowest overpotential of 38 mV and 89 mV to achieve the current density of 10 mA/cm 2 and 100 mA/cm 2 respectively, and long-term stability in acidic electrolyte. To our knowledge, the activity of Fe0.33 Co0.33 Ni0.33 P is superior to most of the known HER catalysts reported to date, proving the feasibility of Fex Coy Niz P to improve HER activity. Graphical abstract: A homogeneous multimetallic phosphides of Fe0.33 Co0.33 Ni0.33 P/CC was rationally designed and fabricated as an excellent and robust electrocatalysts for hydrogen evolution reaction. Highlights: Combined with theoretical prediction, quadruple multimetallic phosphides was prepared. Fe0.33 Co0.33 Ni0.33 P exhibits the lowest overpotential of 38 mV and 89 mV to achieve the current density of 10 mA/cm 2 and 100 mA/cm 2 respectively. The catalyst exhibits outstanding durability and long term stability in acidic electrolyte. The activity of Fe0.33 Co0.33 Ni0.33 P is superior to most of the known HER catalysts reported to date.